Thu gọn biểu thức sau a) f(x) = -3x mũ 2 + x -1 + x mũ 4 – x mũ 3 – x mũ 2 + 3 x mũ 4 b) g(x) = x mũ 4 + x mũ 2 – x mũ 3 + x – 5 + 5x mũ 3 – x mũ 2

Question

Thu gọn biểu thức sau
a) f(x) = -3x mũ 2 + x -1 + x mũ 4 – x mũ 3 – x mũ 2 + 3 x mũ 4
b) g(x) = x mũ 4 + x mũ 2 – x mũ 3 + x – 5 + 5x mũ 3 – x mũ 2

in progress 0
Verity 9 months 2021-04-24T15:33:22+00:00 2 Answers 127 views 0

Answers ( )

    0
    2021-04-24T15:35:03+00:00

    a) `f(x) = -3x^2 + x -1 + x^4 – x^3 – x^2 + 3x^4`

    `f(x) = (-3x^2 – x^2) + (x^4 + 3x^4) + x-1 – x^3`

    `f(x) = -4x^2 + 4x^4 + x-1 – x^3`

    b) `g(x) = x^4 + x^2 – x^3 + x-5 + 5x^3 – x^2`

    `g(x) = x^4 + (x^2 – x^2) -(x^3 – 5x^3) + x -5`

    `g(x) = x^4 – (-4x^3) + x-5`

    `f(x) = x^4 + 4x^3 + x-5`

     

    0
    2021-04-24T15:35:13+00:00

    Đáp án-Giải thích các bước giải:

    a) `F(x)=-3x^2+x-1+x^4-x^3-x^2+3x^4`

    `F(x)=(x^4+3x^4)-x^3+(-3x^2-x^2)+x-1`

    `F(x)=4x^4-x^3-4x^2+x-1`

    b) `G(x)=x^4+x^2-x^3+x-5+5x^3-x^2`
    `G(x)=x^4+(-x^3+5x^3)+(x^2-x^2)+x-5`

    `G(x)=x^4+4x^3+x-5`

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )